2015
DOI: 10.1161/jaha.115.002071
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Aspects of Left Ventricular Mechanical Function Are Differentially Associated With Cardiovascular Outcomes and All‐Cause Mortality in the Community

Abstract: BackgroundThere are few data relating novel measures of left ventricular (LV) mechanical function to cardiovascular disease (CVD) outcomes in the community. Whether distinct components of LV mechanical function provide information regarding risk for different CVD outcomes is unclear.Methods and ResultsWe used speckle tracking echocardiography to quantify distinct components of LV mechanical function (measured as LV strain in multiple planes) in 2831 Framingham Offspring Study participants (mean age, 66 years; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 47 publications
(88 reference statements)
3
85
2
3
Order By: Relevance
“…Thus, additional studies should be performed in other age groups and ethnicities to establish the generalizability of our results. We and others have previously reported on associations of arterial stiffness in relation to adverse cardiovascular events and on the relation of altered myocardial long‐axis strain with all‐cause mortality 4, 65, 66. For the present study sample, in whom both arterial stiffness and myocardial strain measures were performed, the limited number of total events adjudicated to date precludes adequately powered analyses of their combined effects on outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, additional studies should be performed in other age groups and ethnicities to establish the generalizability of our results. We and others have previously reported on associations of arterial stiffness in relation to adverse cardiovascular events and on the relation of altered myocardial long‐axis strain with all‐cause mortality 4, 65, 66. For the present study sample, in whom both arterial stiffness and myocardial strain measures were performed, the limited number of total events adjudicated to date precludes adequately powered analyses of their combined effects on outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to conventional echocardiography together with measurements of LV volumes and EF, the 2D speckle tracking technique opens up the possibility of noninvasively evaluating myocardial deformation (strain). 12 Recent clinical studies explored the prognostic role of these new LV strain indexes. Three studies [5][6][7] in patients with symptomatic HF and reduced EF demonstrated that low LV GLS is superior to EF in identifying patients with poor outcomes, such as all-cause or cardiac mortality and recurrent hospitalization for HF.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 On the contrary, population-based studies are essential to determine the prognostic significance of subclinical LV systolic dysfunction. To date, 2 community-based studies reported on the incremental predictive value of magnetic resonance imaging 11 or echocardioraphically 12 derived LV circumferential strain for incident HF and coronary heart disease. To our knowledge,…”
Section: See Clinical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Several community-based studies [47,64,65] have demonstrated that low global LS is associated with a greater risk for future cardiovascular and cardiac events [47]. For instance, FLEMENGHO participants belonging to the lower quartile of global LS distribution (i.e.…”
Section: Longitudinal Strain and Afterloadmentioning
confidence: 99%